Management of Type 1 Diabetes in Children During the COVID-19 Pandemic in Turkey: Before, During, and After the Lockdown Period - Seda Çağlar; Gamze Kaş Alay; Dilek Sönmez Sağlık; Huriye Karadede (Journal of Diabetology)
Abstract Aim and Objectives: Metabolic control in type 1 diabetes (T1D) depends on many factors such as sleep patterns, eating habits, and exercise. The study aimed to determine the difficulties experienced by Turkish children with T1D and their parents during the COVID-19 pandemic, and the effects of the pandemic on children’s activities of daily living and physiologic parameters. Materials and Methods: This study, which was carried out with a descriptive and retrospective design, was conducted in the pediatric endocrinology outpatient clinic of a university hospital in Turkey. Data were obtained from 38 children with T1D and their parents who were followed up in this clinic between April 2020 and May 2022. Results: The mean age of the children was 14.79 ± 3.05 years, and 65.8% were diagnosed as having T1D 6 years or more ago. When the difficulties experienced by the children during lockdown were examined, it was determined that 50% had difficulties with eating and sleeping patterns. Compared with the other periods, the children’s compliance with diet and regular activity decreased significantly, their sleep duration and screen time increased significantly, and the frequency of communication with peers decreased significantly during lockdown (P < 0.001). It was observed that the mean body mass index (P < 0.001) and HbA1c levels (P = 0.02) of the children increased significantly in the full reopening period after lockdown compared with the prepandemic period and the lockdown period (P < 0.001), and the frequency of blood glucose monitoring was found to be higher during lockdown (P < 0.001). Conclusion: This study reflects how T1D management has changed between prepandemic, lockdown, and postpandemic periods and its impact on children with T1D. It appears that frequent follow-up of children has an effect on their glycemic control as well as long-term physiological parameters including sleep, exercise, and eating patterns.